Growth and Characterization of Glycine Sodium Nitrate as Laser Based Non-Linear Optical Material - PALANISWAMY, S.; BALASUNDARAM, O.N. (Asian Journal of Chemistry, 2010)
Single crystals of glycine sodium nitrate (GSN), a semi organic non-linear optical material has been grown from solution by slow evaporation at ambient temperature. The growth of crystals has been observed at various pH values. The chemical composition of the grown crystals was determined by FTIR spectra. The crystalline nature and its various planes of reflection were observed by powder XRD. The second harmonic generation was also confirmed using Nd:YAG laser.